Relação entre a composição corporal com os sintomas das disfunções do assoalho pélvico e a função da musculatura do assoalho pélvico feminino: estudo transversal - Sousa, Ana Jéssica dos Santos (2023)
Background: Urinary incontinence (UI) is the involuntary loss of urine that may be associated with symptoms related to stress and urgency. It is a clinical condition that impacts the women’s quality of life around the world, with a prevalence of between 25-45%. Obesity and overweight are identified as the main risk factors for UI, therefore improving the assessment of total body composition and in specific regions could help to understand the association between fat and UI symptoms. Thus, a gold standard instrument for assessing body composition, such as dual-emission x-ray densitometry (DXA), can contribute to obtaining important information about the accumulation of total fat and in specific regions, such as the android, visceral, gynoid and pelvic. Objective: To evaluate the intra and inter examiner reliability of pelvic body composition measurements in women based on DXA images; and verify the association between fat located in the android, gynoid, pelvic and visceral regions with female UI symptoms. Materials and Methods: Cross-sectional study performed with women aged 18 and 49. The reliability of the assessment of the pelvic region using DXA was performed by two examiners. Intra-examiner reliability was performed by Examiner 1 who analyzed the image on 2 days separated by a 1-week interval. For inter-examiner reliability, Examiner 2 analyzed the images on a different day than Examiner 1. The intraclass correlation coefficient (ICC) was calculated considering ICC≥0.75 excellent; 0.40≤ ICC <0.75 satisfactory; and ICC <0.40 bad, with a significance level of 5% and a confidence interval of 95%. To assess UI symptoms, participants answered the 3-Incontinence Questions (3IQ-Br), the Urinary Discomfort Inventory (UDI-6) and the Urinary Impact Questionnaire (UIQ-7). Body composition was measured using dual emission X-ray densitometry (DXA). The results of the DXA report of total, android, visceral, gynoid and pelvic fat mass were used. The statistical analyzes used were: descriptive analysis, independent t test, simple logistic regression and multiple linear regression. Results: The intra-examiner and inter-examiner reliability were considered excellent, with ICC above 0.84 (p<0.001) and 0.97 (p<0.001), respectively. Women with stress urinary incontinence (SUI) had a higher concentration of total, android, gynoid and visceral fat (p < 0.05) compared to those who did not report the presence of UI. Univariate regression analysis showed that fat accumulation in the whole body and in the android, gynoid, and visceral regions increased by 0.4; 4.4%, 2.6% and 31.4% times, respectively, the chance of the woman having SUI. In the multiple linear regression model, it was found that visceral fat mass increases the chances of developing SUI by 51% (Odds Ratio 1.51, 95% CI). Visceral fat mass concentration increased discomfort related to urinary symptoms by 16.0% and impact on daily activities in women with urinary symptoms by 9.3%. Conclusion: The intra- and inter-examiner reliability of the Pelvis ROI shows great reliability of the measurement of the pelvic region by DXA images. The accumulation of adipose tissue in the android, gynoid and visceral regions increases the chance of having SUI, however the concentration of visceral fat mass seems to be the factor that is most related to UI and the increase in discomfort and impact on women's daily activities with urinary symptoms.